State of the industry: integration of 3Rs principles and new approach methodologies in non-clinical product development through fit-for-purpose - Sabine M. Poppenborg; Debra Aub Webster; Björn Carlsson (Frontiers in Medicine, 2026)
Regulators, such as the FDA and EMA, are increasingly signaling expectations for broader and earlier adoption of New Approach Methodologies (NAMs) to reduce, refine, and, where justified, replace animal studies (3Rs principle)—particularly where NAMs can deliver improved human relevance, clearer mechanistic insight, or more efficient regulatory decision-making. This creates both an opportunity and a responsibility for drug developers: NAMs should no longer be viewed solely as exploratory tools, but as strategic components of an integrated pivotal non-clinical data package. This is already enshrined in various regulatory guidelines, roadmaps and position papers, but there is no single “approved list” of NAMs for pharmaceutical safety and efficacy assessment that applies across all products and agencies. Regulators explicitly support NAM adoption when scientifically sound, qualified for a defined context of use (COU), and integrated under a weight-of-evidence (WoE) approach. To support drug developers in responding to these expectations, a stepwise approach to expand the use of scientifically validated NAMs, such as in vitro human-based systems (human-organ-on-chip/ microphysiological systems, complex multicellular models, organoids, other 3D systems, and high-throughput screening), in silico methods (e.g., physiologically based pharmacokinetic (PBPK) modeling, machine learning, and computer modeling), and other innovative technologies is provided by authorities. This stepwise approach translates regulatory principles into an actionable pathway for qualifying, implementing, and defending NAMs in safety assessment. Such an approach should define the intended decision and COU, establish pre-specified acceptance criteria and performance expectations, integrate outputs under a transparent WoE framework, and incorporate early health authority engagement to de-risk adoption. The objective is not to promote NAMs as a universal substitute for animal studies but to provide a credible, regulator-aligned route to deploy NAMs where they can meaningfully improve decision quality while reducing animal use. Regulators recommend positioning NAMs as question-driven tools with clearly defined roles, enabling replacement, where performance and regulatory confidence are established, and reduction/refinement, where they optimize study design, dose selection, endpoints, and study sequencing.